CD4+FOXP3+ Regulatory T-Cell Subsets in Human Immunodeficiency Virus Infection - Simonetta, Federico; Bourgeois, Christine (Frontiers in Immunology, 2013)
The role of CD4+FOXP3+ regulatory T cells (Treg) in human immunodeficiency virus (HIV) infection has been an area of intensive investigation and remains a matter of ardent debate. Investigation and interpretation suffered from uncertainties concerning Treg quantification. Firstly, Treg quantification and function in HIV infection remain controversial in part because of the lack of homogeneous and reliable specific markers to identify human Tregs. Secondly, analyzing Treg percentages or absolute numbers led to apparent discrepancies that are now solved: it is now commonly accepted that Treg are targets of HIV infection, but are preferentially preserved compared to conventional CD4 T cells. Moreover, additional uncertainties rely on the duality of immune defects associated to HIV infection, i.e. low grade chronic inflammation and defects in HIV specific responses, which led to consider beneficial and detrimental impact of Treg to the control of HIV infection by suppressing chronic inflammation or HIV specific responses respectively. Indeed both effects of Treg suppression have been described in HIV infection. The discovery in recent years of the existence of phenotypically and functionally distinct human CD4+FOXP3+ Treg subsets may provide a unique opportunity to reconcile contrasting results. It is tempting to speculate that different Treg subsets exert these different suppressive effects. This review summarizes available data concerning Treg fate during HIV infection when considering Treg globally or as subsets. We discuss how the identification of naïve and effector Treg subsets modulates our understanding of Treg biology during HIV infection and the potential impact of HIV infection on mechanisms governing peripheral differentiation of adaptive Tregs.